Rational Design of Donor–Acceptor Based Semiconducting Copolymers with High Dielectric Constants - Mohapatra, Aiswarya Abhisek; Dong, Yifan; Boregowda, Puttaraju; Mohanty, Ashutosh; Sadhanala, Aditya; Jiao, Xuechen; Narayan, Awadhesh; McNeill, Christopher R; Durrant, James R; Patil, Satish (Journal of physical chemistry. C, 2021)
The low dielectric constant of organic semiconductors limits the efficiency of organic solar cells (OSCs). In an attempt to improve the dielectric constant of conjugated polymers, we report the synthesis of three semiconducting copolymers by combining the thiophene-substituted diketopyrrolopyrrole (TDPP) monomer with three different monomeric units with varying electron donating/accepting strengths: benzodithiophene (BBT-3TEG-TDPP), TDPP (TDPP-3TEG-TDPP), and naphthalene diimide (P(gNDI-TDPP)). Among the series, BBT-3TEG-TDPP and P(gNDI-TDPP) exhibited the highest dielectric constants (∼5) at 1 MHz frequency, signifying the contribution of dipolar polarization from TEG side-chains. Furthermore, transient absorption spectroscopic studies performed on these polymers indicated low exciton diffusion length as observed in common organic semiconducting polymers. Our findings suggest that utilizing the polar side-chains enhances the dielectric constant in a frequency regime of megahertz. However, it is not sufficient to reduce the Coulombic interaction between hole and electron in excitonic solar cells.